Noninvasive, Targeted and Non-Viral Ultrasound-Mediated GDNF-Plasmid Delivery for Treatment of Parkinson’s Disease - Fan, Ching-Hsiang; Ting, Chien-Yu; Lin, Chung‐Yin; Chan, Hong-Lin; Chang, Yuan-Chih; Chen, You-Yin; Liu, Hao-Li; Yeh, Chih-Kuang (Scientific reports, 2016)
Glial cell line-derived neurotrophic factor (GDNF) supports the growth and survival of dopaminergic neurons. CNS gene delivery currently relies on invasive intracerebral injection to transit the blood-brain barrier. Non-viral gene delivery via systematic transvascular route is an attractive alternative because it is non-invasive, but a high-yield and targeted gene-expressed method is still lacking. In this study, we propose a novel non-viral gene delivery approach to achieve targeted gene transfection. Cationic microbubbles as gene carriers were developed to allow the stable formation of a bubble-GDNF gene complex and transcranial focused ultrasound (FUS) exposure concurrently interacting with the bubble-gene complex allowed transient gene permeation and induced local GDNF expression. We demonstrate that the focused ultrasound-triggered GDNFp-loaded cationic microbubbles platform can achieve non-viral targeted gene delivery via a noninvasive administration route, outperform intracerebral injection in terms of targeted GDNF delivery of high-titer GDNF genes and has a neuroprotection effect in Parkinson’s disease (PD) animal models to successfully block PD syndrome progression and to restore behavioral function. This study explores the potential of using FUS and bubble-gene complexes to achieve noninvasive and targeted gene delivery for the treatment of neurodegenerative disease.